THE EFFECT OF SCHOOL MANAGEMENT AND STUDENT LEARNING CULTURE ON STUDENT LEARNING EFFECTIVENESS - Delpi LIMBONG; Ihsana El KHULUQO; Istaryatiningtias ISTARYATININGTIAS (Journal of Education and Leadership in Education, 2022)
The effectiveness of student learning in schools is the main responsibility of a leader, where leaders help teachers to do better. Performance appraisals are conducted to tell teachers what management expects to build a better understanding of each other. Assessment must recognize achievement and make plans to improve Student Learning Effectiveness. Research objectives: 1) To find out how much influence school management has on student learning effectiveness. 2) To find out how much influence the Student Learning Culture has on the Effectiveness of Student Learning. 3) To find out how much influence School Management and Student Learning Culture collectively have on Student Learning Effectiveness. This research is a case study research with a survey approach. The sample amounted to 61 people with Use a simple random sample method to determine the sample size. Data is collected through questionnaires and interviews, and data analysis techniques use multiple regression techniques. Conclusion: 1) School management has a positive impact on improving student learning efficiency. 2) Student learning culture has a positive impact on improving student learning efficiency. 3) Have a positive impact on school management and Student Learning Culture together to increase the effectiveness of student learning.